Analisis Peramalan dalam Menentukan Perencanaan Persediaan pada Toko Seragam Sekolah Hermul Jaya - Hidayat, Nurul; Muhammad Ammar Rizki; Ageng Priyo Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Forecasting is an estimation of future events based on systematically compiled past data using certain methods. Forecasting is necessary as a basis for planning, therefore an appropriate forecasting method is needed to see a lower level of error so that inventory planning can be optimal and efficient. This study aims to find a more suitable method to be used at Hermul Jaya Clothing Store to determine the predicted amount of stock in the store. This research uses a descriptive quantitative approach and POM QM application to calculate the inventory forecast of uniform stores based on two indicators, namely Moving Average, Weighted Moving Average and Expponential Smoothing. From the results of this study, the stock inventory at Hermul Jaya Uniform Store is not yet effective because stock purchases or inventory are made without prior planning or it can be said that this store does not use forecasting methods